2016
DOI: 10.1002/ghg.1618
|View full text |Cite
|
Sign up to set email alerts
|

Co‐optimization of CO2‐EOR and storage processes in mature oil reservoirs

Abstract: This paper presents an optimization methodology for CO2 enhanced oil recovery in partially depleted reservoirs. A field‐scale compositional reservoir flow model was developed for assessing the performance history of an active CO2 flood and for optimizing both oil production and CO2 storage in the Farnsworth Unit (FWU), Ochiltree County, Texas. A geological framework model constructed from geophysical, geological, and engineering data acquired from the FWU was the basis for all reservoir simulations and the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…Even though it is expected that most real-world CO 2 storage sites would have a larger effective flow region, such small sites have been used to sequester CO 2 in nonpower plant projects, especially in mature small-to medium-sized enhanced oil/gas recovery projects [53][54][55][56] such as Farnsworth field 57 in Texas, Ketzin 58 in Germany, and other fields 59 from around the world.…”
Section: Site Bmentioning
confidence: 99%
“…Even though it is expected that most real-world CO 2 storage sites would have a larger effective flow region, such small sites have been used to sequester CO 2 in nonpower plant projects, especially in mature small-to medium-sized enhanced oil/gas recovery projects [53][54][55][56] such as Farnsworth field 57 in Texas, Ketzin 58 in Germany, and other fields 59 from around the world.…”
Section: Site Bmentioning
confidence: 99%
“…At present, the fall in oil prices has contributed to the fact that many EOR projects are facing cancellation or delay, but the tertiary techniques including CO 2 -EOR for improving the production of partially depleted reservoirs is still an attractive option. A survey in 2014 showed that miscible CO 2 floods yielded 292,735 bbls per day, which accounted for 38% of oil production for EOR processes in the USA [5][6][7][8][9][10]. The EOR potential evaluation, which assessed more than 200 onshore oilfields of 17 different worldwide oil reserved districts, indicates that China has great EOR potential [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, monitoring and controlling pressure build‐up are crucially important for environmentally safe and efficient implementation of GCS projects . Furthermore, in CO 2 EOR and storage processes, it is important to monitor reservoir pressure to operate within miscibility for avoiding excessive gas production and improving storage . The sensitivity analysis and Monte Carlo sampling results illustrated that porosity, reservoir thickness, and permeability are the key parameters to control CO 2 /water injection and oil production rates in an active CO 2 ‐EOR field …”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, in CO 2 EOR and storage processes, it is important to monitor reservoir pressure to operate within miscibility for avoiding excessive gas production and improving storage. [13][14][15] The sensitivity analysis and Monte Carlo sampling results illustrated that porosity, reservoir thickness, and permeability are the key parameters to control CO 2 /water injection and oil production rates in an active CO 2 -EOR field. 16,17 Extraction of native brine during GCS operations as a pressure management approach has been proposed and can increase storage capacity and effectively diminish the risk of environmental impacts.…”
Section: Introductionmentioning
confidence: 99%